Crisis leadership: a self-study of a novice departmental head - George , Sherronay; Uleanya, Chinaza (Faculty of Teacher Training and Education, Universitas Terbuka, 2024)
Sequel to major changes which occurred due to Covid-19 pandemic, this paper represents a self-study based on a novice departmental head in the educational context. This study focuses on a newly appointed departmental head trying to implement change among teachers with intrapersonal struggles to adapt to change because of their experience, being stagnant and for doing things the same way for over 20 years. The study reflects on leadership style and support provided to teachers during the time of the Covid-19. John Dewey’s reflective process was adopted as framework, and mixed methods approach. Thus, quantitative and qualitative data were collected from eight purposively selected participants. Questionnaire was used to collect quantitative data from six teachers: three experienced and three younger ones, while interviews were conducted for two critical friends in order to collect qualitative data. The collected data were coded and analyzed using themes. The findings of the study showed among others that the newly appointed departmental head empowered and supported all teachers to adapt to change by utilizing the situational theory as a guideline. Thus, support from leaders and involving followers in decision making can change their perceptions with regards to adapting to change and feeling more at ease.